A historical, systematic review of handedness origins. Issue 1 (2nd January 2020) - Marcori, Alexandre Jehan; Okazaki, Victor Hugo Alves
ABSTRACT: Handedness ontogenesis is still under debate in science. This systematic review analyzed articles regarding the theories and basis of handedness formation, highlighting the historical knowledge path that this literature underwent. Cochrane Library, LILACS, Web of Sciences, Science Direct and PubMed databases were searched. This review included review studies with handedness as the main topic. Only papers written in English with analyses exclusively in neurotypical humans (any age range) were included. Different approaches (genetic, neural, social, and behavioural) were reviewed in light of growing evidence, summarizing the current state of the art. Genetic and environmental/social impacts are common points in most of the reviews, each given more or less importance, depending on the author and theory proposed. Multifactorial, developmental approaches to handedness formation seem to be the most up to date view of the phenomenon. Different control mechanisms between hemisphere and neural asymmetries are also contributing factors to handedness formation.